Penyerahan Prasarana, Sarana, dan Utilitas Perumahan dan Permukiman dari Pengembang kepada Pemerintah Daerah (Studi pada Kabupaten Tanah Datar) - Rahmad, Vorry; Warman, Kurnia; Elvardi, Jean (UNES Law Review, 2023)
This research aims to examine and analyze the handover of housing and settlement infrastructure, facilities, and utilities from developers to local governments, as well as legal certainty in the management of the handed-over housing and settlement infrastructure, facilities, and utilities. This research uses empirical juridical methods with primary data collection or processing techniques and interviews with related sources. The results of the research found that the problem that often occurs in the handover of housing and settlement infrastructure, facilities, and utilities from developers to local governments is that regulations regarding the Handover of Housing and Settlement Infrastructure, Facilities, and Utilities have not been disseminated to developers so that to date there has been no handover of infrastructure, Housing and Settlement Facilities and Utilities from Developers to the Tanah Datar Regency Government.